„Srpska, prva faza” suzbijanja epidemija 1914. i 1915. godine - Čukić, Goran (Vojnosanitetski pregled, 2021)
Summary: In the first phase of the suppression of the epidemics before the arrival of Hunter’s mission, the aim of the Serbian Military-medical Corps was to restore its army to readiness in war combat. However, it did not succeed in doing so. In the second phase of suppression, Hunter’s efforts put an end to the epidemics by: a) coordinating activities; b) tightening measures and c) putting into place preventive measures, with means: the "Stammer’s barrel”, the "Serbian barrel". Solutions for topics of military importance were considered immediately, as these assessments were relevant for upcoming military activities. It was necessary to make a decision of utmost urgency as to i) whether the combat readiness of the Serbian army had been restored by the implemented measures, and ii) whether the preventive measures were enough to secure the safe arrival of the allied forces to the areas where there a risk of Epidemic typhus and don’t catch the illness. These decisions were inter-twined because the proven means of suppression could then be used to achieve the next goal. In 1989, Vukšić supported Hunter’s activities and contributions. Hanter’s and Vukšić’s were not detailed interested in "Serbian, first phase". Analyses of the first phase of the suppression of the epidemics indicate that during this period the endeavourses of the Serbian Medical Corps were very significants. Genčić established special preventive measures in both phases, i.e. throughout the entire duration of the epidemics. That indicates “the ineffectiveness of medicine” before the beginning of the epidemics in 1915, which was the main reason for such a large number of casualties. Genčić supported Hunter’s activities. Hunter was assessed as successful while Genčić, his collaborator, was assessed as unsuccessful, which is absurd. The Serbian Military-medical Corps selected the correct strategy, were using chambers with dry warm air, which was his contribution to world medicine in the prevention of Typhus fever. Scientific assessments, and in particular the historical/medical assessments, which were not related to military assessments, could have been made later. It is needed that domestic assessments of events in 1915 are historically/medically re-examined, based on a distinction between the searched ’tags’ for charge and the ineffectiveness of medicine. Key words: special prevention, Typhus, the epidemics of 1915, Hunter, Stammers, Nicolle, Genčić, Batut, Vulović, Vukšić, phases of suppression of the epidemics, the "Serbian barrel", dry warm air chambers, The Military-medical Corps of Serbia